(untitled) (Advancements in Homeopathic Research, 2022)
Homoeopathy is safe and reliable treatment for the flu. A well-chosen homeopathic prescription serves to reinforce the self-healing capacity of the body by boosting the immune system. If we were to draw up a laundry list of common flu symptoms it would read something like this: fever, chills, sweats, aches, fatigue, headache, cough, sore throat, diarrhoea and so on. Since homeopathy is concerned primarily with the unique way in which each individual manifests his or her symptoms, the trick for the prescriber is to determine what symptoms are most prominent, or characteristic, in any given case of the flu. A careful study of the symptom pattern of the sick individual allows the prescriber to choose a corresponding homeopathic medicine that closely matches that pattern.1